2009
DOI: 10.1021/jp806374s
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Conjugated Polyelectrolyte Electron Injection Layers: Effect of Halide Counterions

Abstract: We examine the influence of halide counteranions on the efficiencies of solution-processed multilayer polymer light-emitting diodes (PLEDs) containing cationic conjugated polyelectrolyte (CPE) electron injection layers (EILs). The parent CPE used in these studies is poly[9,9-bis[6′-(N,N,N-trimethylammonium)hexyl]fluorene-alt-co-1,4-phenylene] bromide. Dialysis was used for exchanging counteranions, while X-ray photoelectron spectroscopy (XPS) provides a convenient technique for evaluating the final polymer com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 34 publications
1
33
0
1
Order By: Relevance
“…Materials : PFP‐NR3 and PBS‐PFP, with molecular weights M n ≈ 3500 and 6500 g mol −1 (from gel permeation chromatography),24 respectively, were synthesized as previously reported 10, 43, 44. TEOS and n‐dodecylpentaoxyethylene glycol ether (C 12 E 5 ) were purchased from Aldrich.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Materials : PFP‐NR3 and PBS‐PFP, with molecular weights M n ≈ 3500 and 6500 g mol −1 (from gel permeation chromatography),24 respectively, were synthesized as previously reported 10, 43, 44. TEOS and n‐dodecylpentaoxyethylene glycol ether (C 12 E 5 ) were purchased from Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…This may be particularly important for photovoltaic devices as it may offer a means of minimising the charge carrier diffusion distance between donor and acceptor components. It has recently been observed that the efficiency of cationic CPEs as charge‐transport layers in polymer light‐emitting diodes is strongly influenced by the charge‐compensating counterion present 42, 43. The next step is a systematic study of the interaction of different charged terminal groups at the inorganic‐organic interface to determine if any structure‐activity correlation can be identified.…”
mentioning
confidence: 99%
“…Charge‐compensating counterions should be taken into consideration in the molecular design of CPEs since their properties (size, hydrophobicity, mobility, redox potential, charge density etc.) enable fine‐tuning of the optoelectronic properties both in solution and in the solid state . Bazan and colleagues have notably reported that the solid‐state photoluminescence properties of a cationic CPE based on a poly((9,9‐dihexylfluorene)‐ alt ‐(4,7‐(2′,1′,3′‐benzothiadiazole))) backbone ( PFBT-X ) (Scheme ) can be manipulated by changing the size of the counterion: larger anions lead to increased interchain distance and thereby increased emission quantum yields .…”
Section: Molecular Design and Performance Of Polythiophene Il Materialsmentioning
confidence: 99%
“…enable fine-tuning of the optoelectronic properties both in solution and in the solid state. 90 -93 Bazan and colleagues have notably reported that the solid-state photoluminescence properties of a cationic CPE based on a poly((9,9dihexylfluorene)-alt-(4,7-(2 ′ ,1 ′ ,3 ′ -benzothiadiazole))) backbone (PFBT-X) (Scheme 4) can be manipulated by changing the size of the counterion: larger anions lead to increased interchain distance and thereby increased emission quantum yields. 94 The same authors also showed that replacing the bromide counterion with the larger tetrakis(1-imidazolyl)borate (BIm 4 − ) anion in a cationic narrow bandgap CPE (Scheme 4) derived from the poly((2,6-(4,4bis(2-ethylhexyl)cyclopenta-[2,1-b;3,4-b ′ ]-dithiophene))-alt-(4,7-(2 ′ ,1 ′ ,3 ′ -benzothiadiazole))) (PCPDTBT) framework (Scheme 3) not only modified the HOMO and LUMO energy levels, but also its semiconducting character (p-type for Br − and n-type for BIm 4 − ).…”
Section: Nature Of the Counterionmentioning
confidence: 99%
“…This result is important in view of the application in optoelectronics devices where the formation of an ionic junction, created by the presence of a CPE injection layer, is needed to achieve a better charge injection 37–39. We noticed that the choice of ZW as a complexing agent eliminates the eventual formation of salty inclusions formed by free salts, which would further hinder the formation of ordered structure and also the efficient charge transport in the CPE.…”
Section: Photoluminescence Quantum Efficiencies (Plqe) Of the Blends mentioning
confidence: 99%